Food handlers' practices and associated factors in public food establishments in Gondar, Ethiopia 2021/2022. Issue 4 (April 2023) - Engdaw, Garedew Tadege; Tesfaye, Amensisa Hailu; Worede, Eshetu Abera
Abstract: Food safety is crucial to avoid foodborne illness and improve human wellbeing. Millions of people get sick, and many of them pass away due to eating unhealthy food. Foodborne diseases are still a public health problem in developing countries like Ethiopia. The objective of this study was to assess food handlers' practices and associated factors in public food establishments in Gondar, Northwest Ethiopia. Across-sectional study was conducted among 417 food handlers in food and drink service establishments. The data were collected using a structured interview-administered questionnaire and an observational checklist. Multivariable logistic regression was used to identify predictors. The prevalence of food safety practice among food handlers was 37.6%, with a 95% CI of (32.9, 42.7). More than half of the study participants had good knowledge and attitude. Sex (female) [AOR = 0.40, 95%CI: (0.23, 0.92)], educational status (diploma and above) [AOR = 1.50, 95%CI: (1.21, 3.10)], and good attitude [AOR = 0.25 95%CI: (0.12, 0.89)] were predictors of food safety practices. The prevalence of food safety practices among food handlers in Gondar food establishments was low. The provision of education and on-the-job training on food safety and personal hygiene is advised to enhance good food handling practices.